A body as listening: resonant cartography of music (im)materialities - Sá, Joana 1979- (Lisbon Sistema Solar Ed., 2022)
This book unfolds from the perspective of a musical practice by taking your body as part of this resonant cartography.It will imply exploring all kinds of (im)possible resonant and vibratory processes.All entities responsible for this book cannot, however, predict ‘what a body can do’ or take entire responsibility for ‘its’ actions or outcomes.By navigating the two streams in this book, you agree with the fact that we do not provide the best experience, therefore agreeing to and feeding the possibility of failure.
Text in English
Keywords: Improvisation; Performance art; Body